Reshaping Economic Geography: World Development Report by The World Bank - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Growth is spatially uneven, and the world’s economies would be better off if they don’t fight concentration of economic activity in large cities or leading provinces. Rather, they should embrace the concentration and take advantage of the scale economies, the specialisation, and efficiency that such concentrations bring. This is the principal conclusion of the “World Development Report, 2009: Reshaping Economic Geography”.